Recurrence of suicide attempt in adolescents lost to contact early by clinicians: The 10-year REPEATERS cohort of French adolescents. (August 2015) - Ligier, Fabienne; Guillemin, Francis; Angot, Catherine; Bourion, Stéphanie; Kabuth, Bernard
Abstract: Losing contact with adult suicide attempters in the year after the suicide attempt (SA) increases the risk of recurrence. The situation with adolescents is unknown. We aimed to determine whether being lost to contact early (LCE) by clinicians is a risk factor of long-term SA recurrence among adolescents and the associated factors. Data were collected 10 years after an index SA and a Cox model was used for analysis. Among the 249 SA patients included, 59 (24%) were LCE, the most important risk factor of SA recurrence up to 10 years (hazard ratio [ HR ] = 2.8 [95% confidence interval (95% CI) 1.4–5.5]; p = .016). Risk factors of being LCE were female sex (odds ratio [ OR ] = 2.9 [95% CI 1.1–8.2]; p = .009), a psychiatric comorbidity ( OR = 2.2 [1.1–4.3]; p = .023) and no family history of suicide ( OR = 2.1 [1.1–4.3]; p = .047). These results support the development of preventive actions early after an SA in an adolescent to maintain contact and care.